Ethical, Deontological and Regulatory Challenges in Contemporary Clinical Trials: Implications for Scientific Research Institutions in the EU (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Clinical trials are fundamental to biomedical research, enabling the systematic evaluation of new drugs, devices, and interventions for safety and efficacy. Conducted in progressive phases, they follow rigorous ethical, scientific, and regulatory standards to ensure participant protection and data reliability. Despite their pivotal role in medical innovation, trials are resource-intensive and financially demanding. Ethical frameworks such as the Declaration of Helsinki and Good Clinical Practice guide their conduct, while post-marketing surveillance ensures ongoing safety monitoring. The role of clinical trials, together with their ethical and institutional aspects, is examined with particular attention to current challenges and regulatory developments.